Development Of Mathematics Learning Media Based On Macromedia Flash - Nasution, Muhammad Iqbal (Yana Research, 2022)
This study aims to develop mathematics learning media through macromedia flash on the material of a three-variable linear equation system in class X MA Pondok Pesantren Darul Qur'an. This study also aims to determine the practicality and effectiveness of the developed media. The teaching material presented by the researcher is a system of three-variable linear equations for class X students of MA Pondok Pesantren Darul Qur'an. The subjects in this study were students of class X MIA 3 MA Darul Qur'an Islamic Boarding School. This type of research is development research that refers to a 4D development model that is modified into 3D, namely: the definition stage, the design stage, and the develop stage. The instruments used in this study were validation sheets to measure the validity of the developed learning media, student response questionnaire sheets, teacher response questionnaire sheets, and learning outcomes tests. student. The learning media developed in this study was declared valid, based on the percentage score of eligibility by media experts, namely 75% and by material experts, namely 89% in the very feasible category. From the teacher response questionnaire data, it can also be seen that the teacher assesses the learning media as being very practical with reaching a percentage of 82.5%. And according to student responses, the learning media developed is included in the practical criteria with a percentage of 70%. The developed learning media has met the effective criteria based on the value of the hypothesis test carried out where, t count 14.12 and t table = 1.70. This shows that t count > t table (14.12 > 1.70). Based on the t-test criteria, then H0, rejected as well as accepted Ha. So the alternative hypothesis Ha which states